Uniqueness, stability analysis and approximate solution of a fractional order COVID-19 Model (Journal of Mathematical Modeling and Fractional Calculus, 2024)
In this paper, we investigate a fractional model for the COVID-19 epidemic that contains an  antiretroviral treatment compartment. We implement novel methods to acquire effective results.  We discuss equilibrium point, reproductive number, and sensitivity analysis. We utilize the  Sumudu transform technique to obtain approximate solutions for the model, and we explore  chaos control to assess stability around equilibrium points. We demonstrate the numerical  simulations to prove the accuracy of the proposed techniques. The graphs illustrate how varying  fractional orders impact the dynamics of each epidemiological group, revealing the memory and  time-dependent effects on disease spread and control strategies.
Keywords: Sumudu transform; Uniqueness; Sensitivity Analysis; Numerical Scheme